Mental Accounting Versus the Illusion of Happiness: Understanding Thoughts and Meaning of Happiness from the Side Lifestyle - Marissa Silooy; R. Suryanti Ismail; Gwen L. L. Pattinama (Univiversitas Dr. Djar Wattiheluw, 2024)
This research examines the financial behavior of students at the Indonesian Christian University of Maluku (UKIM) regarding mental accounting in daily life, influenced by lifestyle and perceptions of happiness. Using a qualitative phenomenological approach, data were collected through interviews, categorized by themes, and analyzed. The researchers used key informants for this study, namely 8 students from the Indonesian Christian University of Maluku.Using triangulation techniques to increase validity and reliability. Findings indicate that mental accounting affects financial decision-making and income management among students in boarding houses. It contributes to a sense of happiness as students manage their finances from their parents, showing wise application of mental accounting in financial decisions.